Synthesis and Characterization of Novel Tetradentate ligand Type N4 and its Complexes With CoII,NiII,and PdII. - E. I. Yousif (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
A  new  Schiff base  ligand  [2,3,8,9â€“tetra -phenyl-1,4,5,7,10,12-hexa azo-5,12- dihydro -6,11- dione 1,3,7,10-dudec-tetra-ene]  [H2L]  and  its  complexes In general formula [M(H2L)]Cl2 (where : M= CoII, NiII, and PdII) were prepared. This ligand was prepared in two steps,in the first step a solution of  benzil in methanol was reacted  under  reflux   with    semicarbazidhydrochlorid  to give an (intermediate compound)[benzyl bisâ€“(Semicarbazone)] which was  reacted  in the  second   step with  benzil giving  the  mentioned  ligand. The  complexes CoII, NiII, and PdII were    synthesized  by direct  reaction of the  corresponding  metal  chloride  with  the  ligand [H2L].The  ligand  and  complexes  were  characterized  by spectroscopic methods (IR, UV-Vis, and atomic absorption), chloride content and  conductivity  measurement.From the data  of  these  measurements, we suggestred a tetrahedral  geometry for CoII, NiII complexs and a square planar for PdII complex.